DESIGN OF A DUAL-BAND REJECTION PLANAR ULTRA-WIDEBAND (UWB) ANTENNA - Sahar K. Hassan; Adheed H. Sallomi; Musa H. Wali (Journal of Engineering and Sustainable Development, 2022)
This article discusses about a small Ultra-wideband fix radio wire with two score channels. Spaces are embedded into the fix of the receiving wire to give WiMAX and WLAN recurrence band dismissal. The radio wire is displayed with the economically accessible CST Microwave Studio apparatus. The opening size are steadily changed and tuned to get the ideal band dismissal reactions. The gathered outcomes show that the radio wire capacities admirably across the whole operational frequency spectrum (3.1 GHz to 10.6 GHz), with the exception of the notched WiMAX (3.3-3.7 GHz) & WLAN (5.1-5.8 GHz) bands. Additionally, the antenna was built & the simulation results were gathered.